A history of fashion without fashion: Recovering the stout body in the digital archive. Issue 1 (1st June 2019) - Peters, Lauren Downing
Since its beginnings in the mid-1980s as an interdisciplinary field of study indebted to its more entrenched sister disciplines of costume studies and dress history, fashion studies has witnessed scholars adopt a number of innovative methods and approaches, stemming from fields as disparate as economic history and ethnology. Even amid this diversity of approaches, however, the object – and more specifically, the garment – continues to hold a place of special importance in the minds and research of fashion studies scholars. What happens, however, when the material record is lacking or absent? What methods and resources can fashion scholars employ to reconstruct a history of fashion without fashion?With my doctoral research into the history of the stoutwear industry – the early-twentieth-century predecessor to what is today known as plus-size fashion – serving as a case study, this article will examine how the digital may enable scholars to recover histories of fashion; retrace historical self-fashioning practices; retrieve lost memories; and reconstruct bodies that have been lost due to conventional practices of conservation, collecting and archiving. In addition to describing my process and findings, this article will more generally consider the possibilities, but also the perils, of conducting historical fashion research in the digital realm.